THE STRENGTH CHARACTERIZED BY SPEED OF THE LEGS AND ITS RELATIONSHIP TO THE SKILL OF ROLLING IN FOOTBALL AMONG FOURTH-YEAR STUDENTS - DHI QAR UNIVERSITY - Zainab Hayder Sfayyih (European Journal of Humanities and Educational Advancements, 2023)
The process of reaching the required level in the sports field requires studying all aspects related to raising the level of achievement, whether physical or skillful and others, and knowing the extent to which these aspects relate to each other. The game of football, the physical aspects have a direct contribution, whether public or private, and by following up the practical lectures of football in the College of Physical Education and Sports Sciences / Dhi Qar University, it was noticed that there is a weakness in the performance of the dribbling skill, which is one of the basic and important skills in the game. The study is to identify the relationship between the strength characteristic of the speed of the two men and its relationship to the skill of dribbling in football among the students of the fourth stage, Dhi Qar University.